Perancangan dan Implementasi Website pada TK Kristen Tabqha Kota Batam Menggunakan Metode SDLC - Zhang, Wesley; Sama, Hendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
The rapid advancement of technology that continues to develop at the present time has its roots in the world of education. Tabqha Christian Kindergarten Batam is one part of the Tabqha Education Centre, established in 2008 with a noble goal of providing high-quality formal education based on Christian values to the younger generation in Batam City. One of the issues faced by this school is the lack of technology in delivering information about Tabqha Christian Kindergarten Batam. Based on the existing problem, this research is conducted with the objective of designing and implementing a website for Tabqha Christian Kindergarten Batam that can accommodate information from the school, making it more known within the community. The website design process is carried out using the Software Development Life Cycle (SDLC) method, resulting in a website that will be hosted on Niaga Hoster and provided to the management of Tabqha Christian Kindergarten Batam